Differential Effects of MitoVitE, α-Tocopherol and Trolox on Oxidative Stress, Mitochondrial Function and Inflammatory Signalling Pathways in Endothelial Cells Cultured under Conditions Mimicking Sepsis - Beverley E. Minter; Damon A. Lowes; Nigel R. Webster; Helen F. Galley (MDPI AG, 2020)
Sepsis is a life-threatening response to infection associated with inflammation, oxidative stress and mitochondrial dysfunction. We investigated differential effects of three forms of vitamin E, which accumulate in different cellular compartments, on oxidative stress, mitochondrial function, mRNA and protein expression profiles associated with the human Toll-like receptor (TLR) -2 and -4 pathways. Human endothelial cells were exposed to lipopolysaccharide (LPS)/peptidoglycan G (PepG) to mimic sepsis, MitoVitE, α-tocopherol, or Trolox. Oxidative stress, mitochondrial function, mitochondrial membrane potential and metabolic activity were measured. NFκB-P65, total and phosphorylated inhibitor of NFκB alpha (NFκBIA), and STAT-3 in nuclear extracts, interleukin (IL)-6 and IL-8 production in culture supernatants and cellular mRNA expression of 32 genes involved in Toll-like receptor-2 and -4 pathways were measured. Exposure to LPS/PepG caused increased total radical production (p = 0.022), decreased glutathione ratio (p = 0.016), reduced membrane potential and metabolic activity (both p < 0.0001), increased nuclear NFκB-P65 expression (p = 0.016) and increased IL-6/8 secretion (both p < 0.0001). MitoVitE, α- tocopherol and Trolox were similar in reducing oxidative stress, NFκB activation and interleukin secretion. MitoVitE had widespread downregulatory effects on gene expression. Despite differences in site of actions, all forms of vitamin E were protective under conditions mimicking sepsis. These results challenge the concept that protection inside mitochondria provides better protection.